The impact of supply chain management practices on supply chain management performance in Chinese manufacturing industries - Feng, Shu Fang (2015)
This study attempts to investigate the impact of supply chain management practices on supply chain management performance in Chinese manufacturing industries. A total of 112 respondents from manufacturing industries of Lanzhou the capital city of Gansu is selected and data is analyzed based on the questionnaires. Customer-supplier relationship, information systems and technology, quality management, corporate culture and material flow management are considered as practices and independent variables and only supply chain management performance is assigned as dependent variable. Descriptive analysis, Pearson correlation analysis and multiple regression analysis are utilized to analyze the data and satisfy the objectives of this research as well. The findings reveal that prediction of supply chain management performance is feasible by customer-supplier relationship in which possess highest correlation (r value is 0.809) and linear relationship (r value is 0.281) with supply chain management performance, whereas information systems and technology has lowest correlation (r value is 0.639) and linear relationship (r value is 0.091) with supply chain management performance.